FINANCING OF LABOR RESOURCES IN CONDITIONS OF CRISIS CYCLICITY - ALEKSEYENKO, Lyudmyla; TSIZHMA, Oksana (Scientific journal «World of Finance», 2020)
Introduction. The philosophy of state policy of Ukraine should be aimed at developing the economic potential of the nation and its well-being, the ability of the economy to effectively use and restore labor resources. Therefore, further modernization of labor finance requires the harmonization of economic interests of its participants and the development of society in the context of promoting job creation, business growth and improving the level and quality of life. Purpose. Disclosure of conceptual bases of financing of labor resources in the conditions of crisis cyclicity and delineation of expediency of application of public-private programs for formation of the proper level of economic stimulation and social support of workers. Results. The essence of labor resources financing within the institutional, dialectical, reproductive and systemic approaches is substantiated, taking into account the peculiarities of the labor market development. The economic and social principles of increasing responsibility and trust between the state and citizens in crisis conditions are analyzed, in particular, the intensification of state incentives for employment by fully or partially subsidizing the creation of new jobs in enterprises. There was a significant reduction in the number of economically active population, including employed and unemployed. It was emphasized that this situation was influenced by negative trends in demographic development: population aging, rising mortality, depopulation, deformation of gender and age, migration outflow of able-bodied citizens outside the region. Conclusions. In a market economy, the financing of labor resources should be studied in terms of a set of interconnected elements and subsystems (organizational, technical, managerial, technological, regulatory), which aim to increase the efficiency of the financing process for systemic changes in the environment, including crisis cyclicality. The main components of the state program of labor resources development are determined. To restore labor resources, it is proposed to use public-private programs that provide an opportunity to form an appropriate level of financial incentives and social support for workers. Public-private programs should be structured depending on the level of the subject and the chosen means and tools of material incentives and intangible incentives for employees, improving their professional competencies and professional abilities.